Diagnosis Of Eating of Cutting Tools on The Basis of Analysis of Vibroacoustic Sounds in The Process of Mechanical Processing of Materials - Fayzimatov Boxodir Numanovich; Abdullayev Shuhrat Maxmutjonovich; Abduvoxidov Shaxriyor Zikrullo oʻgʻli (Zien Journals, 2022)
The results of numerical modeling of Vibroacoustic Signal (VAS) in this article provide information on the use of vibroacoustic signal (VAS) parameters describing the dynamics of this process to determine the processing ability of metals by cutting, to determine the cause of the unstable process observed during cutting .
Keywords: acoustic; vibroacoustic; milling; viscosity